الحماية الجنائية للمستهلك من الإشهار الإلكتروني الخادع - - لعطوي الطاهر - رزيقات بشرى (جامعة المسيلة, 2021)
تناولت هذه الدارسة موضوع الإشهار الإلكتروني الخادع وأثره على متطلبات حماية المستهلك من الناحية القانونية، و ذلك إذا ما استعمله المورد الإلكتروني بطريقة تضر بالمستهلك باستخدام طرق احتيالية تتمثل في تضليلهم و تؤدي إلى خداعهم. هذا ما اعتبرته القوانين و الأنظمة بأنه جريمة وجب مواجهتها من خلال ردع وفرض عقوبات جنائية على كل من يرتكبها. حماية المستهلك الإلكتروني من جميع المخاطر التي قد تلحق به في التجارة الإلكترونية، هو أحد مهام ومسـؤوليات الدولـة، وذلك من خلال تنظيم الإشهار الإلكتروني في قانون خاص وتطبيقه على أرض الواقـع، وتحقيق الحماية المنشودة من طـرف المشرع لكافـة أطراف العلاقة الاقتصادية خاصة المستهلك كونه يمثل الحلقة الأضعف في هذه العلاقة. الكلمات المفتاحية: المستهلك الإلكتروني، المورد الإلكتروني، المعلن، الإشهار الإلكتروني، الإشهار الخادع، التجارة الإلكترونية، حماية المستهلك. Abstract: This study dealt with the subject of deceptive electronic publicity and its impact on the legal requirements of consumer protection, if used by the electronic supplier in a way that harms the consumer by using fraudulent methods of misleading and deceiving them, which the laws and regulations have identified as an offence that must be addressed by deterring and imposing criminal penalties on anyone who commits it. The protection of the electronic consumer against all risks to it in electronic commerce is one of the tasks and responsibilities of the State, by regulating electronic publicity in a special law and applying it in practice, and by achieving the desired protection by the legislator of all parties to the economic relationship, especially the consumer, as it represents the weakest link in that relationship. Key words: Consumer Electronics, Electronic Supplier, advertiser, electronic advertising, scam advertising
Keywords: المستهلك الإلكتروني، المورد الإلكتروني، المعلن، الإشهار الإلكتروني، الإشهار الخادع، التجارة الإلكترونية، حماية المستهلك.